The Effect of Preoperative Neutrophil-Lymphocyte Ratio On Quality of Life After Coronary Artery Bypass Graft (CABG) Surgery - Kamal, Fatmawati; Awg Isa, Raihan; Khalid, Zalizah; Mohd Asmawi, Ummi Mohlisi (Environment-Behaviour Proceedings Journal, 2019)
Neutrophil-lymphocyte ratio (NLR) is an inexpensive and easily accessible inflammatory biomarker. Studies have shown the ability of NLR to predict poor outcome in many diseases. This study aimed to determine the relationship between NLR and cardiovascular risk factors, and duration of ICU and hospital stay in post CABG patients. 137 patients who underwent CABG between 2013 and 2017 with available preoperative neutrophil and lymphocyte counts were included in the study. NLR was found to be increased in patients who had prolonged intensive care unit (ICU) stay and hospital/ ward stay. Thus NLR can potentially be used to predict worse outcome. Keywords: Neutrophil-lymphocyte ratio; coronary artery bypass graft (CABG); mortality; length of stay (maximum 4 keywords) eISSN: 2398-4287 © 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i10.1628